Skills gaps in two manufacturing subsectors in Sri Lanka food and beverages, and electronics and Electricals. - Kashiwagi, Yuzuka (Economic working papers., 2020)
Persistent skills shortages have constrained new investments and economic growth in Sri Lanka. This study recommends supply-side responses to increase the quantity and quality of labor in these areas. Its recommendations include raising awareness among young people about the sectors' employment potential, upgrading courses, providing professional development for instructors, and establishing collaborations between businesses and training institutes.